Using EMBL‐EBI Services via Web Interface and Programmatically via Web Services. Issue 1 (30th April 2019) - Madeira, Fábio; Madhusoodanan, Nandana; Lee, Joon; Tivey, Adrian R.N.; Lopez, Rodrigo
Abstract: The European Bioinformatics Institute (EMBL‐EBI) provides access to a wide range of core databases and analysis tools that are of key importance in bioinformatics. As well as providing web interfaces to these resources, web services are available using REST and SOAP protocols that enable programmatic access and allow their integration into other applications and analytical workflows and pipelines. This article describes the various options available to researchers and bioinformaticians who would like to use our resources via the web interface employing RESTful web service clients provided in Perl, Python, and Java, or would like to use Docker containers to integrate the resources into analysis pipelines and workflows. © 2019 by John Wiley & Sons, Inc.